Two new species of chigger mites (Trombidiformes: Trombiculidae: Blankaartia and Euschoengastia) associated with rodents from the Amargosa Valley, Mojave Desert, United States, with the redescription of Euschoengastia fasolla Brennan and Beck, 1955 - Bassini-Silva, Ricardo [UNESP] (2024)
In the present study, we described two new species, Euschoengastia mojavensissp. n. and Blankaartia aurissp. n. collected from rodents in the Amargosa River valley near Tecopa, in Inyo County, California, USA. We also redescribe the most similar Euschoengastia species when compared with the new species, Euschoengastia fasolla Brennan and Beck, 1955, from Berry Springs Nature Reserve, Utah, USA.